The Value Of Shawisha's Struggle In The Novel Mudzakarati Fi Sijn Nisa By El Sadaawi, A Review Of Wallek And Warren's Literary Sociology - Salwa Mufidah Rahmah; Fadlil Yani Ainusyamsi; Mawardi Mawardi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aimed to analyze the values of struggle embodied by the character Shawisha in the novel Mudzakarati fi Sijn an-Nisā’ by Nawal El Saadawi using Wellek and Warren’s sociology of literature approach. The novel represents the social reality of women living within a repressive prison system in modern Egypt under Sadat's regime. This research employed a qualitative descriptive method with textual content analysis of the novel, enabling an in-depth interpretation of Shawisha’s actions, attitudes, and moral choices. The findings revealed that Shawisha embodies several values of struggle, including moral courage, empathy, solidarity, integrity, and symbolic resistance within a patriarchal power structure. Her ambivalent position, as both an institutional rule enforcer and a victim of the patriarchal system, reflects the complexity of power relations and women's non-confrontational strategies to preserve their dignity through everyday ethical actions (everyday resistance). The primary contribution of this study lies in expanding Wellek and Warren’s sociology of the text by integrating feminist ethics of care and power relations theory. Conceptually, it shifts the paradigm from a binary view of oppression to an analysis of peripheral female agents (the enforcer) who navigate moral crises within oppressive state institutions, thereby offering a novel theoretical model for Arab feminist literary studies.